2016
DOI: 10.1080/13552600.2015.1126657
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the literature comparing male non-serial sexual killers and sexual aggressors: examining homogeneous and heterogeneous characteristics of these groups

Abstract: This review explores the current state of knowledge about sexual homicide, which is often based on uncertainties and contradictory assumptions. In the introduction we examine some of the methodological issues, such as low prevalence rates and operationalisation problems, that contribute to the situation regarding the existing knowledge base. The research investigating the key types of sexual homicide and the possible characteristics distinguishing sexual killers from others types of sexual offenders are outlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…These findings are useful to summarize the knowledge available to date as to the differences and similarities between SHOs and NHSOs. However, as mentioned by Stefanska et al (2016), some of these studies present several limitations. For instance, some studies included both serial and non-serial SHOs, despite these two groups of offenders presenting important differences (see James & Proulx, 2014).…”
Section: Differences Between Shos and Nhsosmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings are useful to summarize the knowledge available to date as to the differences and similarities between SHOs and NHSOs. However, as mentioned by Stefanska et al (2016), some of these studies present several limitations. For instance, some studies included both serial and non-serial SHOs, despite these two groups of offenders presenting important differences (see James & Proulx, 2014).…”
Section: Differences Between Shos and Nhsosmentioning
confidence: 99%
“…Findings from these studies were inconclusive as to whether SHOs and NSHOs differed in physical victimization, relationship status at the time of the crime, low self‐esteem, and age at the time of crime (Stefanska et al, ). As to the crime scene behaviors, the analysis by Stefanska et al () revealed that NHSOs were more likely to have committed vaginal penetration, to plan the crime (see Higgs et al, ; Salfati & Taylor, ; Vettor & Beech, ), and to humiliate the victim (Healey, Lussier, & Beauregard, ; Higgs et al, ). The findings were inconclusive as to whether the victim was restrained.…”
Section: Differences Between Shos and Nhsosmentioning
confidence: 99%
See 3 more Smart Citations